Original article: Circulating myeloid and plasmacytoid dendritic cells after allergen inhalation in asthmatic subjects - Farrell, E; O'Connor, T M; Duong, M; Watson, R M; Strinich, T; Gauvreau, G M; O'Byrne, P M (Allergy (Copenhagen), 2007)
Dendritic cells are key contributors to initiation and maintenance of T-cell immunity to inhaled allergen. The purpose of this study was to enumerate the changes in peripheral blood myeloid (mDCs) and plasmacytoid dendritic cells (pDCs), the DCs expressing chemokine receptor 6 (CCR6) and chemokine receptor 7 (CCR7), following diluent and allergen inhalation in asthmatic subjects. Peripheral blood was obtained from 16 allergic asthmatic subjects before and at 0.5, 1, 2, 3, 4, 6, 24, and 48 h after inhaled diluent and allergen challenges. Dendritic cells were enumerated using flow cytometry. Allergen inhalation significantly reduced mDCs at 6 h (21.3 +/- 2.0 vs 15.0 +/- 1.8/microl blood; P < 0.05) and 24 h (21.5 +/- 3.4 vs 16.4 +/- 2.4/microl blood; P < 0.05) after challenge. Circulating pDCs were significantly lower than baseline up to 24 h after both allergen and diluent challenges. There was a significant efflux of CCR6+ mDCs from peripheral blood at 6 h and CCR6+ pDCs at 4 h after allergen challenge, when compared with diluent. There was no difference in the number of circulating CCR7+ mDCs or pDCs after diluent or allergen challenges. Peripheral blood mDCs and CCR6+ mDCs, but not pDCs, are reduced up to 24 h after allergen inhalation. Thus, allergen inhalation causes trafficking of immature CCR6+ DCs from blood into the airway, while that of the trafficking of the mature CCR7+ DCs from the airways into the regional lymph nodes probably occurs through the lymphatic system. [PUBLICATION ABSTRACT]